Impact of Soldiers' Inventories on the Risk of Injury During IED Blast Under a Light Armored Vehicle - BURKACKI, Michał; SUCHOŃ, Sławomir; JOSZKO, Kamil; GZIK-ZROSKA, Bożena; WOJTKOWSKI, Marcin; WOLAŃSKI, Wojciech; GZIK, Marek (Engineering Transactions, 2017)
Model studies concerning the assessment of soldiers’ safety are mainly focused on the examination of vehicle construction and designing energy consuming materials that reduce acceleration pulse affecting soldiers during an explosion. Authors of this paper focus on ergonomic factors that have a significant impact on the safety of the soldiers during the explosion of improvised explosive devices (IED) under the vehicle. The study examined the impact of the equipment carried by the soldiers on the injuries incurred by them. The research was conducted in the Madymo software program. Simulations indicate a high risk of serious head and neck injuries caused by a wrong weapon position.